About a competence and professional trade of specialists in the field of physical culture - F.I. Sobyanin; S.G. Dudkina (Physical Education of Students, 2013)
Correlation of concepts «competence» and «professional trade» is examined. More than 200 sources are studied. The necessity of account for training of athletic personnels of professional fitness and value of professional trade becomes firmly established as to the ultimate goal of forming of specialist in the field of physical culture. Negative tendencies are exposed in maintenance of preparation of specialists and higher professional athletic education in the higher institutes. Culturological and acmeological approach is offered for further strategy of perfection of professional pedagogical preparation of specialists. The stages of forming of specialist are presented on the basis of application of this approach. A necessity is marked at training of personnels oriented on the exposure of features of professional fitness of young people to the professions in the field of physical culture, its initial state and dynamics.